IoT-Enabled Smart Implants Surgery: Revolutionising Precision, Monitoring and Patient Safety - Ramakrishnan, Praveen; Jalaludeen, Abdulkadhar Mohamed; Gnanasekaran, Lalitha; Sundaram, Thanigaivel; Shivani; Chopra, Hitesh (Scripta Medica, 2025)
The integration of Internet of Things (IoT) technology into implant surgery has altered healthcare by transforming implants from passive devices to intelligent, networked systems that enhance surgical outcomes, allow for real-time monitoring, and increase postoperative care. IoT-enabled implants have sophisticated sensors that monitor key indicators such as heart rate, blood pressure, and glucose levels, and send real-time data to cloud-based platforms via secure wireless networks. This enables healthcare personnel to remotely monitor patient states and anticipate issues, allowing for prompt interventions. Smart cardiac pacemakers and defibrillators detect arrhythmias or malfunctions and immediately warn doctors, significantly reducing life-threatening risks. Similarly, IoT-enabled orthopedic implants, such as connected hip and knee replacements, track mechanical strain, joint movement, and degeneration, providing important information about implant longevity and efficacy. These insights enable surgeons to spot early signs of failure, allowing for timely medical intervention and improving long-term patient outcomes. Furthermore, advances in IoT have permitted robotic-assisted operations, increasing implant placement precision through AI-integrated devices that provide real-time feedback during treatments. This is especially useful in delicate treatments like orthopedic or dental surgery, where precise alignment and placement are required.